2009
DOI: 10.1136/ard.2009.120816
|View full text |Cite
|
Sign up to set email alerts
|

Hes1, a new target for interleukin 1  in chondrocytes

Abstract: Hes1 is a novel IL1beta target gene in chondrocytes which influences a discrete subset of genes linked to cartilage matrix remodelling and/or degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Another example of Notch expression mediated by TNF-␣ is observed in a mouse pancreatic cancer model, as demonstrated Maniati and collegues in 2011 (Maniati et al, 2011). It has been reported that IL-1␤ induces Notch targets expression in chondrocytes, by inducing Notch-1 activation with a similar action of TNF-␣ (Ottaviani et al, 2010). In addition of pro-inflammatory cytokines, TGF-␤ has also been shown to directly induce Hes 1 expression.…”
Section: Notch In Monocyte/macrophage Cells Activation and Functionsmentioning
confidence: 83%
“…Another example of Notch expression mediated by TNF-␣ is observed in a mouse pancreatic cancer model, as demonstrated Maniati and collegues in 2011 (Maniati et al, 2011). It has been reported that IL-1␤ induces Notch targets expression in chondrocytes, by inducing Notch-1 activation with a similar action of TNF-␣ (Ottaviani et al, 2010). In addition of pro-inflammatory cytokines, TGF-␤ has also been shown to directly induce Hes 1 expression.…”
Section: Notch In Monocyte/macrophage Cells Activation and Functionsmentioning
confidence: 83%
“…The following synthetic gene‐specific primer sets (Sangon, Shanghai, China) were used for qPCR: MMP‐13 forward, 5‐CACAGCAAGCCAGAATAAAG‐3 and reverse, 5‐CACACATCAGTAAGCACCAAG‐3 (Ottaviani et al . ); β‐actin forward, 5′‐GGCTGTATTCCCCTCCATCG‐3′ and reverse, 5′‐CCAGTTGGTAACAATGCCATGT‐3′. Quantitative real‐time PCR was performed using an iCycler iQ5 real‐time PCR system (Bio‐Rad, Hercules, CA, USA) in the presence of the commercially available SYBR Green PCR MasterMix (Takara, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we found greater induction of phospho-AKT by TNF␣ in Notch2 tm1.1Ecan BMM cultures. Therefore, it is possible that HES1 signals through the PI3K-AKT pathway to enhance osteoclastogenesis and induce IL1␤ (57). IL1␤ is involved in the bone-resorbing activity of osteoclasts and in osteoclast formation (37).…”
Section: Notch2 and Tnf␣mentioning
confidence: 99%